Understanding the Cytomegalovirus Cyclin-Dependent Kinase Ortholog pUL97 as a Multifaceted Regulator and an Antiviral Drug Target - Marschall, Manfred; Schütz, Martin; Wild, Markus; Socher, Eileen; Wangen, Christina; Dhotre, Kishore; Rawlinson, William D.; Sticht, Heinrich (Cells, 2024)
Herpesviral protein kinases, such as the therapy-relevant pUL97 of human cytomegalovirus (HCMV), are important for viral replication efficiency as well as pathogenesis, and represent key antiviral drug targets. HCMV pUL97 is a viral cyclin-dependent kinase (CDK) ortholog, as it shares functional and structural properties with human CDKs. Recently, the formation of vCDK/pUL97–cyclin complexes and the phosphorylation of a variety of viral and cellular substrate proteins has been demonstrated. Genetic mapping and structural modeling approaches helped to define two pUL97 interfaces, IF1 and IF2, responsible for cyclin binding. In particular, the regulatory importance of interactions between vCDK/pUL97 and host cyclins as well as CDKs has been highlighted, both as determinants of virus replication and as a novel drug-targeting option. This aspect was substantiated by the finding that virus replication was impaired upon cyclin type H knock-down, and that such host-directed interference also affected viruses resistant to existing therapies. Beyond the formation of binary interactive complexes, a ternary pUL97–cyclin H–CDK7 complex has also been described, and in light of this, an experimental trans-stimulation of CDK7 activity by pUL97 appeared crucial for virus–host coregulation. In accordance with this understanding, several novel antiviral targeting options have emerged. These include kinase inhibitors directed to pUL97, to host CDKs, and to the pUL97–cyclin H interactive complexes. Importantly, a statistically significant drug synergy has recently been reported for antiviral treatment schemes using combinations of pharmacologically relevant CDK7 and vCDK/pUL97 inhibitors, including maribavir. Combined, such findings provide increased options for anti-HCMV control. This review focuses on regulatory interactions of vCDK/pUL97 with the host cyclin–CDK apparatus, and it addresses the functional relevance of these key effector complexes for viral replication and pathogenesis. On this basis, novel strategies of antiviral drug targeting are defined.<br
Keywords: herpesviral protein kinases; human cytomegalovirus; cytomegaloviral vCDK/pUL97; regulation of viral replication; impact of vCDK/pUL97; cyclin H and CDK7; antiviral approaches with kinase inhibitors; novel targeting strategies